2020
DOI: 10.5194/hess-24-3933-2020
|View full text |Cite
|
Sign up to set email alerts
|

A coupled atmospheric–hydrologic modeling system with variable grid sizes for rainfall–runoff simulation in semi-humid and semi-arid watersheds: how does the coupling scale affects the results?

Abstract: Abstract. The coupled atmospheric–hydrologic modeling system is an effective way to improve the accuracy of rainfall–runoff modeling and extend the lead time in real-time flood forecasting. The aim of this study is to explore the appropriate coupling scale of the coupled atmospheric–hydrologic modeling system, which is established by the Weather Research and Forecasting (WRF) model and the gridded Hebei model with three different sizes (1 km×1 km, 3 km×3 km and 9 km×9 km). The Hebei model is a conceptual rainf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In this study, the data to get designs storm are based on WRF rainfall products simulated at high spatial-temporal resolutions to capture localized storm events. The WRF model is robust and flexible in reproducing rainfall data at the spatial and temporal resolution that can be needed for the flood hydrology model (Liu et al 2012;Chawla et al 2018;Tian et al 2020). Here, we simulated four known events (i.e., 25 June 2012, 3 September 2013, 13 April 2016, and 16 April 2016 that have caused distinct flood hazards in Kampala, Uganda.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the data to get designs storm are based on WRF rainfall products simulated at high spatial-temporal resolutions to capture localized storm events. The WRF model is robust and flexible in reproducing rainfall data at the spatial and temporal resolution that can be needed for the flood hydrology model (Liu et al 2012;Chawla et al 2018;Tian et al 2020). Here, we simulated four known events (i.e., 25 June 2012, 3 September 2013, 13 April 2016, and 16 April 2016 that have caused distinct flood hazards in Kampala, Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the WRF model is able to consider the local-scale processes affecting the rainfall, such as the effect of urban extent and position on extreme rainfall distribution (Paul et al 2018;Zhang et al 2018;Oliveros et al 2019). In the same way, the WRF model is robust in considering the variability of the storms across wide areas and its flexibility to reproduce rainfall data at the spatial and temporal resolution that can be needed for the flood hydrology model (Liu et al 2012;Chawla et al 2018;Tian et al 2020). Thus, when appropriately configured and validated, the WRF model is a suitable tool for simulating the high-intensity rainfall events and spatial variability for flood modeling (Zittis et al 2017;Sikder and Hossain 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The value of T in the Fuping and Zijingguan catchments were statistically analyzed. Experimentation demonstrated that the cumulative distribution curves of T values between different regions are always similar [50].…”
Section: The Grid-based Hebei Modelmentioning
confidence: 90%
“…The grid-based Hebei model adopts a simplified form of the Saint Venant equations for confluence calculation. Due to perennial channel water shortage and substantial channel seepage in the study area, an additional Horton infiltration equation was considered in the grid-based Hebei model [50].…”
Section: The Grid-based Hebei Modelmentioning
confidence: 99%
“…Liu et al [26] modified the Green-Ampt equation in the MISDc model to improve flood simulation with fixed values of the maximum water capacity parameter (W_max) but the improvement was minuscule, where the evaluation index (NSE) increased from 0.71 to 0.73. In this study, in an attempt to improve the infiltration process, the emphasis on the impact of W_max calibration was carried out due to its important role in estimating infiltration capacity, which influences the calculation of runoff generation [55]. The improvements were obvious, where the evaluation indexes increased from 0.56 to 0.81 for R 2 and from 0.41 to 0.82 for KGE.…”
Section: The Importance Of W_max Parameter Estimation In Flood Simulamentioning
confidence: 99%